Chemokine Receptor-6 Promotes B-1 Cell Trafficking to Perivascular Adipose Tissue, Local IgM Production and Atheroprotection - Srikakulapu, Prasad; Upadhye, Aditi; Drago, Fabrizio; Perry, Heather M.; Bontha, Sai Vineela; McSkimming, Chantel; Marshall, Melissa A.; Taylor, Angela M.; McNamara, Coleen A. (Frontiers in Immunology, 2021)
Chemokine receptor-6 (CCR6) mediates immune cell recruitment to inflammatory sites and has cell type-specific effects on diet-induced atherosclerosis in mice. Previously we showed that loss of CCR6 in B cells resulted in loss of B cell-mediated atheroprotection, although the B cell subtype mediating this effect was unknown. Perivascular adipose tissue (PVAT) harbors high numbers of B cells including atheroprotective IgM secreting B-1 cells. Production of IgM antibodies is a major mechanism whereby B-1 cells limit atherosclerosis development. Yet whether CCR6 regulates B-1 cell number and production of IgM in the PVAT is unknown. In this present study, flow cytometry experiments demonstrated that both B-1 and B-2 cells express CCR6, albeit at a higher frequency in B-2 cells in both humans and mice. Nevertheless, B-2 cell numbers in peritoneal cavity (PerC), spleen, bone marrow and PVAT were no different in ApoE-/-CCR6-/- compared to ApoE-/-CCR6+/+ mice. In contrast, the numbers of atheroprotective IgM secreting B-1 cells were significantly lower in the PVAT of ApoE-/-CCR6-/- compared to ApoE-/-CCR6+/+ mice. Surprisingly, adoptive transfer (AT) of CD43- splenic B cells into B cell-deficient µMT-/-ApoE-/- mice repopulated the PerC with B-1 and B-2 cells and reduced atherosclerosis when transferred into ApoE-/-CCR6+/+sIgM-/- mice only when those cells expressed both CCR6 and sIgM. CCR6 expression on circulating human B cells in subjects with a high level of atherosclerosis in their coronary arteries was lower only in the putative human B-1 cells. These results provide evidence that B-1 cell CCR6 expression enhances B-1 cell number and IgM secretion in PVAT to provide atheroprotection in mice and suggest potential human relevance to our murine findings.